Nutritional Composition of Marine Water Fishes of Bangladesh: A Review - Rahman, Md. Hafizur; Sultana, Mst. Sharmin; Shelly, Nasrat Jahan; Rahman, Md. Sajedur (International Journal of Bio-resource and Stress Management, 2024)
Marine fishes have been recognized for high quality protein and essential fatty acids which play a vital role in human being for nutrition and disease prevention. This review focuses on the nutrient composition of marine fishes in Bangladesh. Nutrient composition data was collected through literature searching in databases and source, including PubMed, Web of Science, Google Scholar, Science Direct, World Fish, and Bangladesh-based database Banglajol. Published articles contained proximate composition, vitamins, minerals and fatty acids profiles of marine fishes. The highest energy, protein, fat and ash content in 100 g edible raw marine fish was 926 kJ, 50 g, 24.2 g, and 8.4 g, respectively. The maximum amount of minerals such as 8.6 mg iron, 29.3 mg zinc, 1900 mg calcium, 160 µg iodine, 120 µg selenium, 1000 mg phosphorus, 187.98 mg magnesium, 497.4 mg sodium, 764 mg potassium, 1.1 mg manganese, 300 mg sulphur and 0.5 mg copper found in 100 gram edible raw marine fishes. The highest quantity of vitamins was 288.7 µg vitamin A, 0.9 mg vitamin B6, 15 µg vitamin B12, 13 µg vitamin D, 2.4 mg vitamin E, 17 µg folate, 0.2 mg thiamine, 0.2 mg riboflavin and 19.3 mg niacin in 100 gram edible raw marine fishes. According to available data, marine fish are good sources of protein, vitamins, zinc, calcium, phosphorus and fatty acids. This illustrates the diversity in nutrient content of fish species which should guide policy and programs to improve food and nutrition security in Bangladesh.